ChemInform Abstract: A Straightforward Access to Photochromic Diarylethene Derivatives via Palladium‐Catalyzed Direct Heteroarylation of 1, 2‐Dichloroperfluorocyclopentene. Issue 14 (20th March 2013) - Beydoun, Kassem; Roger, Julien; Boixel, Julien; Le Bozec, Hubert; Guerchais, Veronique; Doucet, Henri
Abstract Di‐heteroarylation of 1, 2‐dichloroperfluorocyclopentene (I) is achieved using thiazoles, thiophenes, or furan substituents.